Human Capital Perspectives on Organizational Culture, Work Environment, and Career Development: Mediating Role of Job Satisfaction in Enhancing Employee Performance at PT PLN Persero UPT Gresik - Pamungkas, Luky; Suarmanayasa, I Nengah; Heryanda, Komang Krisna (International Journal of Economics Development Research (IJEDR), 2025)
PT PLN (Persero) UPT Gresik faces several human capital challenges, including a misalignment of organizational culture, a less conducive work environment, and suboptimal career development practices. These issues negatively affect job satisfaction and, in turn, hinder employee performance. This study aims to examine the influence of organizational culture, work environment, and career development on employee performance, with job satisfaction acting as a mediating variable, within a human capital framework. A quantitative approach was employed using a structured questionnaire distributed to employees. The population consisted of 149 employees, with 43 respondents selected through Slovin’s formula. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique. The findings revealed that: (1) organizational culture and work environment have a positive and significant effect on job satisfaction; (2) career development does not significantly affect job satisfaction; (3) organizational culture and career development positively and significantly influence employee performance; (4) work environment has no significant effect on performance; (5) job satisfaction significantly improves employee performance; and (6) job satisfaction mediates the effects of organizational culture and work environment on performance, but not the effect of career development.